2018
DOI: 10.4038/ijms.v5i2.104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Compliance with Principles on Board of Directors and Corporate Performance: Empirical Evidence from Sri Lankan Listed Companies

Abstract: Board of directors in corporate governance is conceptualized as the perceived ability of a firm to constrain and direct corporate power so that it efficiently creates economic value and equitably distributes economic wealth. Accordingly, this study examines the relationship between the level of compliance with the principles on corporate governance related to the board of directors and corporate performance of listed firms in Sri Lanka using secondary data related to 133 listed companies from 2009 to 2016. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, Madi et al (2014) and Albitar (2015) provided evidence that the AC size positively influences the disclosure level. By contrast, Mangena and Pike (2005), Alsaeed (2006), Mangena and Tauringana (2007), Othman et al (2014), Juhmani (2017), Sellami and Fendri (2017) and Dissanayake and Balasundaram (2019) found that there is an insignificant relationship between AC size and disclosure level.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 83%
“…However, Madi et al (2014) and Albitar (2015) provided evidence that the AC size positively influences the disclosure level. By contrast, Mangena and Pike (2005), Alsaeed (2006), Mangena and Tauringana (2007), Othman et al (2014), Juhmani (2017), Sellami and Fendri (2017) and Dissanayake and Balasundaram (2019) found that there is an insignificant relationship between AC size and disclosure level.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 83%